1996
DOI: 10.1152/jappl.1996.81.1.133
|View full text |Cite
|
Sign up to set email alerts
|

In-flight and postflight changes in skeletal muscles of SLS-1 and SLS-2 spaceflown rats

Abstract: Spacelab Life Sciences-1 and -2 provided skeletal muscles from rats dissected in flight for the first time and 2 h to 14 days postflight. The muscles permitted the distinguishing of primary adaptations to microgravity from secondary reloading-induced alterations. In microgravity, rats adopted bipedal forelimb locomotion with the hindlimbs relegated to grasping activities. On landing day, body posture was abnormally low and walking was stilted at a rate one-third of normal. The adductor longus (AL) and soleus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
3
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 0 publications
4
75
3
1
Order By: Relevance
“…During weight bearing, exercise by movement can also take place. Riley et al 19) , however, have reported that rats after re-weighting moved little, when their responses were studied on video tape. Also in the present study, the animals moved little during the weight bearing periods, except for the short period immediately after the beginning of weight bearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During weight bearing, exercise by movement can also take place. Riley et al 19) , however, have reported that rats after re-weighting moved little, when their responses were studied on video tape. Also in the present study, the animals moved little during the weight bearing periods, except for the short period immediately after the beginning of weight bearing.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of space medicine, studies have been conducted concerning disuse syndrome induced under conditions of microgravity 1)4) 19) . Although bed rest and stays in space differ in their background, their symptoms have many similarities.…”
mentioning
confidence: 99%
“…These disruptions to the normal structure and function of muscle are apparent within minutes after injury and may become more extensive during the following hours to days [2,[4][5][6]. Muscle injury also typically causes edema and the extravasation of neutrophils followed by ED1 ϩ macrophages and later the proliferation of resident ED2 ϩ macrophages [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we tested whether modifying NO production in vivo affects muscle inflammation and necrosis or influences the occurrence of inflammatory cell apoptosis during modified muscle use. Rats were subjected to periods of muscle unloading followed by reloading, which has been shown previously to cause muscle inflammation and necrosis [2,5,6] and inflammatory cell apoptosis [29]. Experimental manipulations were performed on animals to which NOS inhibitors were administered, and the concentrations of neutrophils, macrophages, necrotic fibers, and apoptotic inflammatory cells were compared to control animals not receiving NOS inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in muscle structure and function have been well-documented and recent studies have confirmed that these changes are significant (Caiozzo et al, 1996;Riley et al, 1996;Allen et al, 1996). Oxidative damage to mitochondrial DNA also correlates with substantial loss of muscle function in a variety of human diseases and possibly during aging (Wallace, 1992;, so it is quite possible that radiation-induced oxidative stress in muscle tissue during travel in outer space could contribute to muscle atrophy.…”
Section: Is There Synergy Between Radiation and Microgravity?mentioning
confidence: 99%